Giant iron-ore deposits of the Hamersley province related to the breakup of Paleoproterozoic Australia: new insights from in situ SHRIMP dating of baddeleyite from mafic intrusions - Muller, S.; Krapez, Bryan; Barley, M.; Fletcher, Ian (Geological Society of America Inc, 2005)
Banded iron formations of the ca. 2770-2405 Ma Hamersley province of Western Australia were locally upgraded to high-grade hematite ores during the Early Paleoproterozoic by a combination of hypogene and supergene processes after the initial rise of atmospheric oxygen. Ore genesis was associated with the stratigraphic break between the Lower and Upper Wyloo Groups of the Ashburton province, and has been variously linked to the Ophthalmian orogeny, late-orogenic extensional collapse, and anorogenic continental extension. Small-spot in situ Pb/Pb dating of baddeleyite by sensitive high-resolution ion microprobe (SHRIMP) has resolved the ages of two key suites of mafic intrusions, constraining for the first time the tectonic evolution of the Ashburton province and the age and setting of iron-ore formation. Mafic sills dated as ca. 2208 Ma were folded during the Ophthalmian orogeny and then cut by the unconformity at the base of the Lower Wyloo Group. A mafic dike swarm that intrudes the Lower Wyloo Group and has a close genetic relationship to iron ore is ca. 2008 Ma, slightly younger than a new syneruptive 2031 ± 6 Ma zircon age for the Lower Wyloo Group. These new ages constrain the Ophthalmian orogeny to the period between ca. 2208 and 2031 Ma, before Lower Wyloo Group extension, sedimentation, and flood-basalt volcanism. The ca. 2008 Ma dikes pre s ent a new maximum age for iron-ore genesis and deposition of the Upper Wyloo Group, thereby linking ore genesis to a ca. 2050-2000 Ma period of continental extension similarly recorded by Paleoproterozoic terrains worldwide well after the initial oxidation of the atmosphere by ca. 2320 Ma.